Case Note: Another Chapter in the Cassirer Nazi-era Art Saga Focuses on Choice of Law. Issue 4 (8th December 2015) - Frey, Laurie
Abstract: In June 2015, a United States district court in California found that the Madrid-based Thyssen-Bornemisza Collection Foundation had acquired ownership of a Camille Pissarro painting under Spanish adverse possession law. Unless overturned on appeal, the decision will end the long-running efforts by the heirs of Lilly Cassirer Neubauer to recover the painting, which was wrongfully taken by the Nazis. The decision to apply Spanish law determined the outcome of the case, and the court's discussion of choice-of-law issues is notable given the decisive effect that the applicable law often has in art and cultural property ownership disputes. After describing the background and reasoning of the case, this case note comments on two interesting aspects of the decision: its discussion of choice of law in the context of suits against foreign government entities and its treatment of a recent amendment to California law intended to make it easier to recover stolen art.